Strategic options and their impact on the financial structure - Case Study Neftal Tebessa Company - - Daas, mossaab; farid, aimen (Journal of Research in Finance and Accounting, 2020)
The aim of this study is to try to explain the relationship between the structure of the financial structure and the strategic financial decisions and the knowledge of all types of financial decisions in the economic institution, as well as to clarify the impact of the strategy on the financial structure. Based on the above, we conducted the field study at the Naftal-Tebessa Foundation during the period 2016-2018, based on the financial budgets. The results of the study showed that the institution is characterized by financial stability and financial independence. On the expansion strategy. We also concluded that the relationship between the financial structure and the strategic choice in the institution is a fit relationship, that is, one can be built on the other, since the institution, by relying on a strategic option, affects its financial structure.